Proposed new interior design of HR Spa And Retail for HR Marketing Sdn.Bhd at 2-G, Jalan Reko Sentral 6,43300, Kajang / Hazmira Omar - Omar, Hazmira (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learns from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose a new interior design of HR Spa and Retail for HR Marketing Sdn. Bhd at 2-G, Jalan Reko Sentral 6, 43300,Kajang, Selangor Darul Ehsan. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the faith in the customers and the workers in HR Spa and Retail. Connected to that, the chosen design style for HR Spa and Retail is based on rustic and nature design, the client’s needs as they want the spa centre to have the rustic nature look and at the same time would attract the customers to attend. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services offered, products of the brand, spaces to be concluded in the proposed area, operation time and information about other spas that use the same system in management as the proposed spa. Some of the gained information of the study is through interviews, printed media, internet, observation and through the result from the case study either locally or internationally. It is hope that this report will benefit all the readers whether directly or indirectly.